Chaplain and psychiatrist as ally-rivals - Tiedeman, Gary H. (Journal of religion and health, 1982)
Chaplain and psychiatrist share professional concern for the improved psychological health of the distressed general hospital patient. Commonality of concern suggests regular consultative co-presence and associated interprofessional collaboration. This study of consultation within one teaching hospital finds that co-presence occurs in less than five percent of potential cases and that collaborative exchange in connection with those cases is rare, a condition supported by psychiatric staff and found regrettable by chaplains. "Case-typing," guided by outlooks of secularization (chaplain), scientism (psychiatrist), and traditionalism (ward internist), provides an accounting of collaborative underutilization, supplemented by considerations of organizational structure and positional power.